2014
DOI: 10.5603/fm.2014.0061
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prenatal exposure to bisphenol a on the vagina of albino rats: immunohistochemical and ultrastructural study

Abstract: (Folia Morphol 2014; 73, 4: 399-408)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
(48 reference statements)
1
3
0
Order By: Relevance
“…In general there was sever keratinization (hyper keratosis), epithelial atrophy and many cells completely degenerated, in addition to focal patches of decreasing of epithelial lining. These results came in harmony with study done by Ahmed et al (2014) who reported that exposure to BPA both in low environmental and high doses exerted degeneration of the vaginal epithelium with desquamation, hydropic degeneration and pyknosis. With high dose of BPA, there was extensive desquamation in addition to nearby areas of reactive thickening.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In general there was sever keratinization (hyper keratosis), epithelial atrophy and many cells completely degenerated, in addition to focal patches of decreasing of epithelial lining. These results came in harmony with study done by Ahmed et al (2014) who reported that exposure to BPA both in low environmental and high doses exerted degeneration of the vaginal epithelium with desquamation, hydropic degeneration and pyknosis. With high dose of BPA, there was extensive desquamation in addition to nearby areas of reactive thickening.…”
Section: Discussionsupporting
confidence: 90%
“…BPA significantly downregulates their expression, leading to striking morphologic changes in the differentiation and cornification of vagina (Schönfelder et al 2010). Estrogen receptor α (ERα) down-regulation seems to be responsible for the observed altered vaginal morphology (Ahmed et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Ahmed et al examined the morphological changes of the vagina after BPA exposure in rats, and the results showed that 0.1 mg/kg BPA treatment reduced the upper layer of the local vaginal plaque, whereas 50 mg/kg BPA directly caused the foamy cytoplasmic vacuolation and the pyknotic nuclei of the epithelial nucleus in the vagina, which might further lead to vaginal tumor lesions [ 293 ]. Both BPA and BPF exposure could alter the secretion function of vaginal epithelial cells in mice and lead to increased vaginal mucus [ 294 , 295 ].…”
Section: Toxic Effects Of Bisphenols On Other Female Reproductive Organsmentioning
confidence: 99%
“…Alterations in other reproductive tissues were also noted upon treatment with BPA. For example, prenatal BPA exposure in rhesus macaque altered the percentage of different cells in the fetal oviduct [27], and exposure of albino rats to BPA led to the degeneration of the vaginal epithelium [28]. In addition, CD1 mice treated with BPA exhibited uterine polyps and sarcoma of the uterine cervix [29].…”
Section: Introductionmentioning
confidence: 99%